Analysis of Video Traveloka Advertisements Entitled “Dari Monoton Jadi Seru-Seruan” and “Badri and Aldi” Using Multimodal Discourse Theory - Yohana Yohana; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2021)
In the marketing world, there are a lot of competitors who compete their business to become the number one. Thus, some companies want to make their product exist in the customer's mind by making a video advertisement which usually appears on television or social media platforms. By making video as the instrument of advertisement, usually some companies can share a particular message about their brand or product to their customer. The message is used to persuade the people who see the advertisement to buy their product. Commonly, the video advertisement contains elements of semiotic resources such as visual, audio, oral, spatial, linguistic, and gesture. Those elements help the audience to understand particular messages. In this thesis, the researcher aims to reflect the message of fun traveling moment in Traveloka video advertisements by looking at the elements of semiotic resources which are divided into two parts, they are verbal and non-verbal expression and find out the brand image of Traveloka video advertisement by looking at interrelatedness of the some semiotic resources. The researcher used two videos of Traveloka advertisements as the object of analysis, then the writer found out the verbal and non-verbal expressions which convey the message using the theories of Multimodal discourse and the writer interpreted the message using a descriptive qualitative research method. According to the researcher's analysis, she finds that both two videos of Traveloka advertisements reflect fun traveling moments which can be seen through the combination of some semiotic resources and find two brand images of Traveloka such as having quality time and seeking meaning of life. Keywords: Advertisement, Verbal, Non Verbal, Semiotic, Traveloka, Multimodal